2011
DOI: 10.1117/12.872939
|View full text |Cite
|
Sign up to set email alerts
|

Short wavelength limitation in high power AlGaInP laser diodes

Abstract: In wavelength region of red color, luminous efficacy rapidly increases as wavelength shortens. In that sense, red laser diode (LD) with shorter wavelength is required for display applications. Experimental results for short wavelength limitation in AlGaInP LDs are shown and discussed in this paper. Broad area LDs with 625, 630, and 638 nm are successfully fabricated. Operation current versus output power (P-I) characteristics and its temperature dependence of 625 nm LD are inferior to that of 630 and 638 nm on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, the T 0 value of free-running GaInNAs diode is suppressed due to the low front-facet reflectivity [ 10 ] and can thus be improved by providing the wavelength locking optical feedback from Bragg grating in nonlinear waveguide [ 11 ]. In addition, it is known that the performance of AlGaInP-based laser diodes, especially their T 0 values, deteriorate strongly as the wavelength is decreased towards 620 nm [ 4 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the T 0 value of free-running GaInNAs diode is suppressed due to the low front-facet reflectivity [ 10 ] and can thus be improved by providing the wavelength locking optical feedback from Bragg grating in nonlinear waveguide [ 11 ]. In addition, it is known that the performance of AlGaInP-based laser diodes, especially their T 0 values, deteriorate strongly as the wavelength is decreased towards 620 nm [ 4 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…While we were able to reduce the vertical far field in contrast to a previous publication [10] with θ vert-FWHM = 31° at a similar wavelength, the other parameters were only slightly reduced, showing that a good material quality can be maintained. However, others reported somewhat higher T 0 values of 39.5 K even at continuous wave operation [9], so further improvements should be feasible and special care needs to be taken in the cooling of the current lasers.…”
Section: Vertical Structure and Materials Parametersmentioning
confidence: 98%
“…Especially for red-emitting lasers the efficiency strongly depends on the wavelength [2,3,4,5]. It has been shown that for the red color diode lasers the optimum wavelength is in the region between 630 nm and 640 nm [6,7,8,9,10]. Diode lasers are sought for display application due to their small size, high efficiency, direct analog electrical modulation capability, and general reliability.…”
Section: Introductionmentioning
confidence: 99%
“…While the red-green gap has been shrinking in the last years with ever longer wavelength InGaN lasers [1] and shorter wavelength InGaP/GaAs based designs [2,3] a wavelength range between 550 nm and 600 nm is still not covered with commercial laser diodes. Hence, direct single-pass frequency doubling (SHG) of infrared diode laser is an appealing method to reach this spectral region, because it allows unprecedented degrees of miniaturization and efficiency, while allowing direct modulation up to the MHz.…”
Section: Introductionmentioning
confidence: 99%